Pilot study of the short-term effects of range-of-motion exercise for the temporomandibular joint in patients with temporomandibular joint disc displacement without reduction - Sakuma, Shigemitsu (J Phys Ther Sci, 2017)
[Purpose] This study investigated the effectiveness of a short-term exercise program combining range-of-motion exercise for the temporomandibular joint and self-traction therapy in patients with temporomandibular joint disc displacement without reduction. [Subjects and Methods] The study participants comprised 36 females with jaw trismus and moderate to severe functional pain. The range-of-motion exercise for the temporomandibular joint was performed at the first visit by the therapist, and the patients were instructed to perform self-traction therapy in the morning and during daily bathing until the next visit 2 weeks later. Maximum mouth opening distance and the visual analogue scale score were used to compare pain on motion and mastication as well as the impact of the program on daily activities at the first consultation and 2 weeks later. [Results] All symptoms were significantly improved after 2 weeks of treatment. [Conclusion] A program that combines exercise for the temporomandibular joint and self-traction therapy can improve range of motion at the joint in the short term and reduce pain and difficulty associated with daily activity in patients with temporomandibular joint disc displacement without reduction. The results of this study suggest that such a program can serve as an effective conservative treatment.